Drug warriors and their prey from police power to police state - Miller, Richard Lawrence (Praeger, 1996)
Miller not only argues that criminal justice zealots are harming the democracy they are sworn to protect, but that authoritarians unfriendly to democracy are stoking public fear in order to convince citizens to relinquish traditional legal rights. Those are the very rights that thwart implementation of an agenda of social control through government power. Miller contends that an imaginary "drug crisis" has been manufactured by authoritarians in order to mask their war on democracy. He not only examines numerous civil rights sacrificed in the name of drugs, but demonstrates how their loss harms ordinary Americans in their everyday lives